Effect of therapeutic exercises on the development of the working muscles on the details of the hip joint by partial absorption of the crescent in students of the College of Physical Education and Sciences Sports / University of Sulaimani - Muhammad, Asst.L.Zendi Jalal; Qadir, Asst.L.Briar Othman (Sulaimani Journal for Humanities, 2026)
Preparation or training for exercise often falls under the term "sports medicine" and is considered a rehabilitative form of treatment. In this form, the therapist and patient work together to improve physical condition through strength, endurance, and safe exercises to facilitate the client's entry into more demanding physical activity. The goal of therapeutic exercises is to restore the body to its natural state and eliminate the dysfunction of the injured part. Partial meniscus tears are more common among students in particular, and there is a lack of attention to a comprehensive program for strengthening the body's muscles and a lack of use of rehabilitative exercises specialized in treating muscle strains in the lower extremities in general and the thigh muscles in particular. The importance of this research lies in developing a rehabilitation program using isometric and isotonic contraction exercises to rehabilitate meniscus injuries in the knee joints. The researchers used a single-group experimental design with pre-test and post-testing, as it was suitable for the nature of the research problem. The research sample consisted of five students with meniscus tears in their knee joints. The training program was implemented during a special preparation period of six weeks, with three rehabilitation units per week on Saturdays, Mondays, and Wednesdays, totaling 18 rehabilitation units. The researchers used the SPSS statistical package to analyze the results. The researchers concluded that the scientifically based therapeutic exercises helped increase mobility and thigh muscle strength in the injured students, and that isometric and isotonic contraction exercises played a role in improving partial meniscus tears in the knee joints.